DISPARITAS PERTUMBUHAN EKONOMI DAN PEMBANGUNAN EKONOMI WILAYAH DI SATUAN WILAYAH PEMBANGUNAN IV PROPINSI JAWA TIMUR - Siswoyo Hari Santosa (MediaTrend, 2015)
Regional economic growth structure  in Regional Unit Development (RUD) IV East Java Province are different. It is caused by different of natural resources, demography, and different potential of its regional so it can make the disparity of economical development. This research uses secondary data PDRB to know how the economical development structure, the best sector, and the disparity level that is occur in each regional. Shift Share-Esteban Marquillas Analysis showed that in Jember, Bondowoso, and Situbondo Regional  occur the changing of dominant sector that dominated by agricultural (primary sector) to tertiary sector due to the conversion of agricultural land to non-agricultural sector . Disparity in development using williamson index analysis , the results fluctuated with a declining trend and has an average inequality is quite low . Overall position of the economy in the district of East Java in the RUD IV included in the relatively underdeveloped regions. Based on the relationship between economic growth and development imbalances stated that the Kuznets hypothesis ( curve U - Reversed ) turned out to be valid in the RUD IV East Java Province.